A behavioural game-theoretic analysis of hedge fund regulation. Issue 7 (24th May 2018) - Fairchild, Richard
ABSTRACT: We analyse the efficacy of hedge fund regulation in a behavioural game-theoretic model consisting of two players: a hedge fund manager and a regulator. The regulator decides whether or not to regulate hedge fund strategies, and location of key service providers (KSPs). The manager then decides (a) which KSP to choose, (b) whether to choose a safe or risky strategy, and (c) how much effort to exert in affecting the strategy's success probability. We consider the effect of expected future fund flows on the manager's incentives. Furthermore, we consider economic and behavioural factors affecting the regulator's decision-making. Finally, we discuss how our two cases (myopic versus far-sighted managerial behaviour) may inform the debate over regulation over the entire financial market-cycle. Overall, our analysis contributes to the debate on hedge fund regulation.